Produção de cachaça - BALSI, Luiz Fernando Vieira (173, 2022)
O Brasil é o maior produtor de cana de açúcar do mundo, esta cultura além de ser utilizada para a produção de etanol, açúcar e energia, também se destina para a produção de cachaça. Denomina-se Cachaça toda bebida tipicamente brasileira, produzida pela destilação do caldo de cana-de-açúcar fermentado, com graduação alcoólica entre 38 e 48% em volume a 20°C com características sensoriais peculiares. É a segunda bebida mais consumida no mercado brasileiro (volume que corresponde a 50% do volume do segmento de destilados), e o terceiromaior destilado do mundo. Vale lembrar que na produção de cachaça a qualidade deve estar presente nos cuidados com o solo e com o plantio da variedade apropriada de cana-de-açúcar, passando por todas as etapas de fabricação até a comercialização deste produtoO envelhecimento da cachaça é uma prática que possibilita a modificação da sua cor, sabor e aroma. Isso acontece em função dos diversos tipos de madeiras e suas habilidades de mudarem as características sensoriais da bebida. Este trabalho faz uma breve revisão bibliográfica, sobre a produção de Cachaça, ele foi desenvolvido em nível de pesquisa bibliográfica, onde a bibliografia constitui uma fonte de informações com dados já organizados e analisados, como livros, periódicos, entre outros. Neste contexto foi mostrado a importância do processo fermentativo para a produção de um produto de excelência para apreciação e comercialização.

Brazil is the largest producer of sugar cane in the world, this culture, in addition to being used for the production of ethanol, sugar and energy, is also intended for the production of liquor. of fermented sugarcane juice, with an alcohol content between 38 and 48% by volume at 20°C with peculiar sensory characteristics. It is the second most consumed beverage in the Brazilian market (volume which corresponds to 50% of the volume of the distillates segment),and the third largest distillate in the world. It is worth remembering that in the production of cachucha, quality must be present in the care of the soil and with the planting of the appropriate variety of sugarcane, going through all the stages of manufacture until the commercialization of this product. This work makes a brief bibliographic review on the production of liquor, it was developed at the level of bibliographic research, where thebibliography constitutes a source of information with data already organized and analyzed, such as books, periodicals, among others. In this context, the importance of the fermentation process was shown for the production of a product of excellence for appreciation and commercialization. The aging of liquor is a practice that allows the modification of its color, flavor and aroma. This is due to the different types of wood and their ability to change the sensory characteristics of the drink. And all this according to the taste of the producer and, of course, the consumer. The distillation process has as main objective to separate and concentrate the volatile compounds present in the wine from the residual fraction called vinasse.
Cachaça production
Keywords: Biocombustíveis; Cachaça; Produção Industrial